HEROIC-PATRIOTIC EDUCATION OF STUDENTS - A RELIABLE BASIS OF SPIRITUAL GROWTH AND SELF-DEVELOPMENT OF PERSONALITY (Pedagogy of Higher and Secondary Education, 2022)
This article is dedicated to the heroic — patriotic bringing of the pupils as a reliable basis of spiritual growth and self - development of personality.
Keywords: general values of the mankind; citizen; patriot; social bringing-up